Evaluating the Diagnostic Yield of Computed Tomography-Guided Aspirations in Suspected Post-operative Spine Infections. Issue 2 (July 2016) - Jo, Jonathan E.; Miller, Andy O.; Cohn, Matthew R.; Nemani, Venu M.; Schneider, Robert; Lebl, Darren R.
Background: Early detection of surgical site infection (SSI) following spinal surgery would allow for prompt treatment and would improve overall outcome, yet early diagnosis is a challenge. Computed tomography (CT) guided aspiration of fluid collections may aid in diagnosis, as its diagnostic utility has previously been demonstrated in the setting of hip SSI, knee SSI, and spontaneous diskitis. There is no literature on its use in post-operative spinal SSIs. Questions/Purposes: The current study aims to (1) determine the diagnostic value of CT-guided aspiration in evaluating suspected SSI; (2) identify the characteristics of the clinical presentation that are predictive of SSI; and (3) identify characteristics of the hematologic workup that are predictive of SSI. Methods: Thirty patients who underwent CT-guided aspiration of paraspinal post-operative fluid collections and culture of aspirate fluid over the 6-year period from 2006 to 2011 were retrospectively reviewed. Aspirate fluid culture results were compared to intraoperative cultures, which were used as the "gold standard" for diagnosing SSI. The diagnostic value was evaluated by determining the sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of aspirate fluid cultures. Clinical presentation, patient demographics, comorbidities, and laboratory values were reviewed for association with infection risk. Results: Eleven of thirty patients undergoing CT-guided aspiration were subsequently confirmed to have SSI through positive cultures. Wound drainage, wound erythema, elevated ESR, and cloudiness of aspirate fluid were associated with SSI. The sensitivity and specificity of aspirate cultures were 36.4 and 89.5%, respectively, and the respective positive predictive value (PPV) and negative predictive value (NPV) were 66.7 and 70.8%. Conclusions: Cloudy aspirate fluid was highly suggestive of infection, while wound erythema, drainage, and elevated ESR were also suggestive of SSI. CT-guided aspirations are a useful adjunct tool in evaluating for SSI but further studies are necessary before it can be considered a stand-alone diagnostic procedure.